Who's afraid of aggregating money metrics? - Kristof Bosmans; Koen Decancq; Erwin Ooghe (Theoretical Economics, 2018)
We provide an axiomatic justification to aggregate money metrics. The key axiom requires the approval of richer-to-poorer transfers that preserve the overall efficiency of the distribution. This transfer principle - together with the basic axioms of anonymity, continuity, monotonicity, and a version of welfarism - characterizes a standard social welfare function defined over money metric utilities.
Keywords: D61; D63; D71; I31; 330; Money metric utility; transfer principle; efficiency